Psychometric Properties of an Arabic Version of the Intolerance of Uncertainty Scale - Alatrany, Saad Sabet Jaber (International Journal of Psychosocial Rehabilitation, 2020)
Introduction: Literatures have clearly demonstrated that intolerance of uncertainty may be a key factor in developing various mental disorders (for example, depression, anxiety and posttraumatic stress disorder. This study aimed to examine the psychometric properties of an Arabic version of intolerance of uncertainty (IUS). Methods: (578) undergraduate students were recruited and completed a questionnaire to measure depression and anxiety as well as IUS. Results: The IUS had excellent internal consistency (α=.89) with significant correlations between items and total scores of IUS. Factor analysis resulted a four-factor solution. In addition, there were significant correlations among IUS and depression and anxiety. Conclusion: The Arabic version of IUS seems an acceptable scale to assess IU and intolerance of uncertainty has good relationships with depression and anxiety.